Characterization of Sodium Soaps and their Refractive Index Studies in Methanol - Varma, R.P.; Kumar, U.; sangal, Prerna (Asian Journal of Chemistry, 2010)
Sodium soaps (abietate, oleate and myristate) have been prepared and their characteristics in solid state have been studied by I.R. methods to obtain structural information. The critical micelle concentration (C.M.C.) has been determined by refractive index and the values of molar refraction of soap, [R]2, have been calculated.